INVESTIGATION OF BENTONITE CLAY SURFACE AS A PHYSICAL ANTIDOTE IN ADSORPTION OF AMITRIPTYLINE-HCl, CHLORPROMAZINE-HCl AND CHLORDIAZEPOXIDE-HCl FROM SOLUTION - SAADOON A. ISA; SAMEER M. JASSIM (College of Pharmacy University of Baghdad, 2017)
ABSTRACT: A detailed study of adsorption from solution of amitriptyline-HCl, chlorpromazine-HCl and chlordiazepoxide-HCl on bentonite clay surface has been performed at variable conditions of temperature, pH and ionic strength. It is aimed in this work to explore the capability of this clay in treatment of poisoning by the mentioned drugs if taken in quantities higher than the usual doses. Quantities of drugs adsorbed have been determined by UV spectrophotometric technique. The sequence of adsorption in neutral media at 37.5 Ù'C followed the order: Amitriptyline-HCl > chlorpromazine-HCl > chlordiazepoxide-HCl. The results were discussed in the light of Langmuir and Freundich adsorption isotherms. The usual basic themodynamic functions were estimated.